Highly sensitive sensing of zinc(II) by development and characterization of a PVC-based fluorescent chemical sensor - Aksuner, Nur; Henden, Emur; Yenigul, Berrin; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Pergamon-Elsevier Science Ltd, 2011)
A sensor membrane with excellent performance based on 1-methyl-1-phenyl-3-[1-hydroxyimino-2-(succinimido)ethyl]cyclobutane has been developed for the determination of zinc(II) ions. The sensing membrane is capable of determining zinc(II) with an outstanding high selectivity over a dynamic range between 8.0 x 10(-8) and 1.6 x 10(-4) mol L(-1) with a limit of detection of 2.5 x 10(-8) mol L(-1)(1.6 mu g L(-1)). It can be easily and completely regenerated by using 0.1 mol L(-1) EDTA solution. The optical sensor developed here was found to be stable, cost effective, easy to prepare, and has unique selectivity towards Zn(2+) ion with respect to common metal ions. The proposed sensor was then applied for the determination of zinc in tap water and hair samples with satisfactory results. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: PVC matrix; Fluorescence spectroscopy; Optical sensor; Zinc(II)